The Effects of Storage on Sachet Water Quality in Ogun State, Nigeria - ZO Ajekunle; VO Ojekunle; AO Eruola; FF Oyebanji; KA Olatunde; BT Amujo; OR Sangowusi; AA Adekttan; AG Taiwo (Journal of Applied Sciences and Environmental Management)
The purpose of this study is to investigate the effect of storage on the physicochemical status and bacteriological quality of sachet water produced and sold in  Abeokuta metropolis, Nigeria. Ten brands of sachet water were collected within 24 hours of production and stored at ambient temperature. Sub-samples were drawn from the stock samples immediately for physico-chemical and microbiological analyses and after two months. Physical parameters were determined by instrumental methods. Cationic and anionic constituents were determined by standard titrimetric and spectrophotometric methods, trace and heavy water were determined by Atomic Adsorption Spectrophotometer. The study revealed that all the brands of water analyzed were physically and chemically wholesome and met the WHO standards. Five brands (50%) of the water had total viable and coliform count above the recommended count of 100cfu/m and zero cfu/ml, respectively. pH values increased in all brands to acceptable WHO limits within 2 months of storage except for sample 3 and 4 which decreases below the acceptable limit.  Majorly dissolved oxygen and nitrate values decreased through the investigation period. Total and faecal coliform appeared in 50% of sachet water samples  analyzed immediately after production and were no longer detected after storing for two months except for sample 4. Results of the experiment indicate that 60% of the brands analyzed met the WHO guideline limit for drinking especially for the physico-chemical parameters while the majority failed in the microbiological essay when stored at ambient temperature for the two-month investigation period.